2020
DOI: 10.3390/ma13194259
|View full text |Cite
|
Sign up to set email alerts
|

Real-Time Optimization of Anti-Reflective Coatings for CIGS Solar Cells

Abstract: A new method combining in-situ real-time spectroscopic ellipsometry and optical modeling to optimize the thickness of an anti-reflective (AR) coating for Cu(In,Ga)Se2 (CIGS) solar cells is described and applied directly to fabricate devices. The model is based on transfer matrix theory with input from the accurate measurement of complex dielectric function spectra and thickness of each layer in the solar cell by spectroscopic ellipsometry. The AR coating thickness is optimized in real time to optically enhance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 32 publications
0
8
0
Order By: Relevance
“…Each of the innovative solutions is designed to limit the optical losses to a specific area; however, they can be combined to maximize the PCE of the cell. The substitution of conventional metal contacts with interdigitate contacts and the use of an antireflective layer on top of the window layer improve the transmission of the light to the active layer. , Other changes in the basic structure relate to the use of new materials as a window layer, buffer layer, or electron back reflector (EBR). The recent study by Olivier et al details many other light management strategies applicable to CIGS-based ultrathin cells as well as their limitations.…”
Section: Technology and Manufacturing Processmentioning
confidence: 99%
“…Each of the innovative solutions is designed to limit the optical losses to a specific area; however, they can be combined to maximize the PCE of the cell. The substitution of conventional metal contacts with interdigitate contacts and the use of an antireflective layer on top of the window layer improve the transmission of the light to the active layer. , Other changes in the basic structure relate to the use of new materials as a window layer, buffer layer, or electron back reflector (EBR). The recent study by Olivier et al details many other light management strategies applicable to CIGS-based ultrathin cells as well as their limitations.…”
Section: Technology and Manufacturing Processmentioning
confidence: 99%
“…[106] To find the AR layer optimal thickness value, all the inactive layers that act as an obstacle between air and CIGS have to be considered. [107,108] Rajan et al demonstrated the dependence of the optimal MgF 2 thickness value on the individual solar cell layers' thickness variation: CIGS absorber (500-2500 nm), the CdS buffer (20-90 nm), and the AZO window (150-300 nm). [108] To do so, the authors used a transfer matrix theory optical model combined with in situ real-time spectroscopic ellipsometry measurements, while depositing the AR layer, to measure the unpolarized reflection as a function of the AR thickness.…”
Section: Front Light Management Strategiesmentioning
confidence: 99%
“…[107,108] Rajan et al demonstrated the dependence of the optimal MgF 2 thickness value on the individual solar cell layers' thickness variation: CIGS absorber (500-2500 nm), the CdS buffer (20-90 nm), and the AZO window (150-300 nm). [108] To do so, the authors used a transfer matrix theory optical model combined with in situ real-time spectroscopic ellipsometry measurements, while depositing the AR layer, to measure the unpolarized reflection as a function of the AR thickness. With such an approach, both theoretical models and experimental results demonstrated that as the individual solar cell layers thickness values are modified, the optimum MgF 2 thickness has to be adjusted to achieve a minimum reflectance.…”
Section: Front Light Management Strategiesmentioning
confidence: 99%
“…In some instances, an anti-reflection layer is also deposited, which increases the amount of light that reaches the absorber layer and therefore increases the device efficiency. The layer is ~100 nm thick [146,147] and magnesium fluoride (MgF2), aluminium oxide (Al2O3) and cerium fluoride (CeF3), for example, can be used [148]. One method of deposition is via electron beam evaporation [146,147],…”
Section: The Transparent Conducting Oxidementioning
confidence: 99%
“…The layer is ~100 nm thick [146,147] and magnesium fluoride (MgF2), aluminium oxide (Al2O3) and cerium fluoride (CeF3), for example, can be used [148]. One method of deposition is via electron beam evaporation [146,147],…”
Section: The Transparent Conducting Oxidementioning
confidence: 99%